2023
DOI: 10.1097/js9.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

The surgical patient of yesterday, today, and tomorrow—a time-trend analysis based on a cohort of 8.7 million surgical patients

Abstract: Background: Global healthcare delivery is challenged by the aging population and the increase in obesity and type 2 diabetes. The extent to which such trends affect the cohort of patients the authors surgically operate on remains to be elucidated. Comprising of 8.7 million surgical patients, the American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) database can be analyzed to investigate the echo of general population dynamics and forecast future trends. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Our findings suggest that more vulnerable perioperative patients flow through our (tertiary) hospitals, which is in line with previous investigations 10 13 , 24 , 26 . Adding to this—perhaps expected finding—is the fact that when adjusting for age, acuity and illness severity, improved outcomes are seen over the study period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings suggest that more vulnerable perioperative patients flow through our (tertiary) hospitals, which is in line with previous investigations 10 13 , 24 , 26 . Adding to this—perhaps expected finding—is the fact that when adjusting for age, acuity and illness severity, improved outcomes are seen over the study period.…”
Section: Discussionsupporting
confidence: 93%
“…A UK study has reported that high-risk patients accounted for 12.5% of surgical procedures but for 80% of postoperative deaths 6 . Knoedler and colleagues reported recently that the median age of the American surgical cohort increased by 3 years 2008–2020, and forecasted it to continuously rise until 2030, with the surgical cohort aging at a faster rate than the global population 24 . A national Swedish study found an annual increase in surgical incidence 2006–2013, with incidence rates peaking in the elderly 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent forecasting analysis involving more than 8 million surgical patients, our group showed that the surgical population is continuously aging. We projected that this aging trend will continue over the next decade, with the median patient age expected to reach 61.5 years by 2030, marking a 5.5‐year increase from 2020 (Knoedler et al, 2023). These findings may directly impact clinical care since aging and frailty are interwoven with multiple studies highlighting age and frailty as surgical risk factors (Aquina et al, 2017; Chung et al, 2021; Cooper et al, 2016; Maloney et al, 2020; Matsuo et al, 2018; Østergaard et al, 2020; Panayi et al, 2021; Panayi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cancer related incidence and mortality is increasing as the global population ages [ 1 , 2 ]. Furthermore, older cancer patients usually have different treatment plan compared to normal cancer patients [ 3 , 4 ]. For instance, patients (≥80 years) with muscle-invasive bladder cancer were recommend to receive bladder-preservation therapy rather than standard radical cystectomy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%